SENAM VITALISASI OTAK: UPAYA EFEKTIF MENGUATKAN FUNGSI KOGNITIF, MENURUNKAN HIPERTENSI DAN EMOSIONAL PADA LANSIA - Wiratma, I Wayan; Maba, I Wayan; Wiryawan, I Gede; Vipriyanti, Nyoman Utari (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Aging is a life process characterized by decreased cognitive function. The decline in cognitive function will affect the health and quality of life of a person and their participation in society. One of the efforts to improve cognitive function is to do brain vitalizing exercises. Research Objectives: To determine the effectiveness of vitalizing brain exercise on cognitive function, hypertension and emotional. Research Methods This research design is included in the pre-experimental research design with one-group pretest-posttest design. This study used purposive sampling. The total population is 100 people and is strictly selected according to the inclusion criteria, namely seniors aged 60 years and over, seniors who are willing to be respondents, elderly people who are included in dementia sufferers, hypertension and emotional disturbances according to the interpretation of the mini mental state examination, blood pressure and geriatric depression scale, leaving 40 respondents. Interventions were carried out 24 times for 30 minutes in 8 weeks. The data were tested using a non-parametric statistical test, namely the Wilcoxon Rank Test. Results: the results of the mini mental state examination obtained p value = 0.00, meaning p 0.05 so that Ha is accepted and Ho is rejected, the hypothesis of the geriatric depression scale obtained p value = 0.00, meaning p 0.05 so that Ha is accepted and Ho is rejected, the hypothesis of hypertension is p = 0.000, meaning p 0.05 so that Ha is accepted and Ho is rejected Conclusion Brain vitalization exercise is effective to reduce cognitive function (dementia), hypertension and emotional mental disorders . Suggestion